Kritik Terhadap Pandangan Joel B. Green Mengenai Monism - Pieter Kurnia; Benyamin Intan (STTRII, 2021)
Green claims that monism is far more consistent than the separation of body and soul, also known as dualistic. Green said humans are whole humans and have no metaphysical aspects. All